Development of Interactive E-LKPD Assisted by QR Code on Two Variable Linear Equation System (SPLDV) Material at Mts Al Fauzi Cinta Rakyat - Fadira, Tri Nurul; Elfrianto, Elfrianto (Jurnal Riset Ilmu Pendidikan, 2025)
Development of Interactive E-LKPD Assisted by QR Code on Two-Variable Linear Equation System Material (SPLDV) at MTs Al Fauzi Cinta Rakyat. This study aims to produce an Interactive E-LKPD product Assisted by QR Code on Two-Variable Linear Equation System Material. This study is a type of development research using 4-D (four-D) research procedures, namely the definition stage, design stage, development stage, and disseminate stage. The subjects of this study consisted of 3 validators, namely material expert validators and media expert validators, consisting of 2 mathematics lecturers and 1 mathematics teacher. In addition, the study was also conducted on 22 class VIII students of MTs Al Fauzi Cinta Rakyat. The results of this study: 1) Researchers have produced interactive E-LKPD assisted by QR Code on the material of two-variable linear equation system; 2) The results of the E-LKPD assessment from material experts were 96% with a very valid category and the results of the E-LKPD assessment from media experts were 91% with a very valid category; 3) The results of the assessment trial through the student response questionnaire obtained an average percentage of 93.95% with a very positive category. Based on the assessment results from material experts, media experts, and student responses, the E-LKPD product developed is valid and suitable for use as teaching materials in mathematics learning.